1981
DOI: 10.1093/bja/53.9.927
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Meptazinol and Pethidine Given I.V. On Demand in the Management of Postoperative Pain

Abstract: Meptazinol and pethidine were compared under double-blind conditions in 20 patients, using an on-demand analgesic system to provide pain relief after upper abdominal surgery. The degree of analgesia, subjectively assessed, was good with both meptazinol and pethidine; although meptazinol produced significantly more nausea than did pethidine (P less than 0.01), there was no statistically significant difference in the frequency of other side-effects. Over 24 h average consumption of meptazinol was 2.4 times that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

1982
1982
1994
1994

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(5 citation statements)
references
References 14 publications
1
4
0
Order By: Relevance
“…The tramadol/pethidine potency ratio, although obtained on relatively few patients, can be accepted with reasonable confidence. The mean 24 h consumption of pethidine at 606 mg closely matches our previous findings for the mean consumption of pethidine after cholecystectomy of 595 mg [2], 570 mg [3] and 614 mg [4] in three double-blind trials. It also accords with a 1 : l ratio found in another similar trial by Lehmann et al [17].…”
Section: Discussionsupporting
confidence: 88%
“…The tramadol/pethidine potency ratio, although obtained on relatively few patients, can be accepted with reasonable confidence. The mean 24 h consumption of pethidine at 606 mg closely matches our previous findings for the mean consumption of pethidine after cholecystectomy of 595 mg [2], 570 mg [3] and 614 mg [4] in three double-blind trials. It also accords with a 1 : l ratio found in another similar trial by Lehmann et al [17].…”
Section: Discussionsupporting
confidence: 88%
“…The role of these other mechanisms, which are thought to be mediated through cholinergic systems, is not clear in man. It has been shown to be effective in postoperative pain [38] by parenteral administration and has a potency approximately similar to that of pethidine. It is well absorbed rectally, but it has been shown that a dose of 150 mg by this route is not adequate for treatment of pain on the first day following hysterectomy [23].…”
Section: Opioid Agonist/antagonistsmentioning
confidence: 99%
“…6 However, it has dropped below this level within one minute of the administration of the suxamethonium. This may offer an explanation for the reduction of muscle fasciculations but not for any therapeutic effect of magnesium on pain.…”
Section: Discussionmentioning
confidence: 96%